Analyzing the Operations at a Textile Manufacturer’s Logistics Center Using Lean Tools - GÜNAY, AHMET CAN; ÖZBEK ,ONUR; MUTLU, FİLİZ; AKTİN, AYŞE TÜLİN (Springer Science and Business Media Deutschland GmbH, 2024)
Compliance with delivery times is crucial for businesses in the logistics sector. Numerous research has been conducted to improve distribution performance. Many of these studies touch on lean production as well. The strategies used in lean manufacturing are often employed by businesses and have a positive impact on performance. This study focuses on the overseas shipping department of a textile company’s logistics center. Workflow starts with product acceptance from manufacturers and ends with shipment to customers abroad. After a thorough examination, some bottlenecks that increase delivery times are observed. Value Stream Mapping (VSM), which is a lean manufacturing technique, is chosen as the main method to be used. It aims to determine value added and non-value-added activities, resulting in minimizing or eliminating the non-value-added ones. Initially, necessary data are gathered through workshops and interviews, and observations on Current State VSM are made. During these workshops, various improvements are proposed and evaluated together with the company’s engineers. After takt time and cycle time calculations, label change station is identified as the bottleneck. In the next step, Kaizens are suggested for the stations, and some lean techniques are employed to solve different workflow problems. Finally, short-term applicability of proposed improvements is discussed, and Future State VSM is drawn. It can be concluded that significant improvements are achieved especially in lead time, changeover time, productivity rate and production speed. By reducing or eliminating non-value-added activities and identifying deficiencies that slow process flow, a standard, sustainable and developable process is proposed to the company. © 2024, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
12th International Symposium on Intelligent Manufacturing and Service Systems, IMSS 2023
📚 Part of the book series: Lecture Notes in Mechanical Engineering ((LNME)).
Keywords: Lean Logistics; Lean Manufacturing Tools; Operation Analysis; Optimization